The Taskforce to now – Have we made progress? - Cosman, Mike (New Zealand Journal of Health and Safety Practice, 2024)
The journey to improved outcomes for workers and others is a long and winding road that seems to expand as some risks improve and others materialise. Disasters, new laws and regulatory restructure have a limited impact, but the underlying challenges remain. In this article the author reviews one part of that journey in New Zealand from 2012 to now but draws on his experience of over 45 years working in this field in the UK, including internationally and in New Zealand since 2004 and reflects on the successes and opportunities that lie ahead.